2020
DOI: 10.3390/land9120503
|View full text |Cite
|
Sign up to set email alerts
|

Physical Crust Formation on Sandy Soils and Their Potential to Reduce Dust Emissions from Croplands

Abstract: The sandy croplands in the Free State have been identified as one of the main dust sources in South Africa. The aim of this study was to investigate the occurrence and strength of physical soil crusts on cropland soils in the Free State, to identify the rainfall required to form a stable crust, and to test their impact on dust emissions. Crust strength was measured using a fall cone penetrometer and a torvane, while laboratory rainfall simulations were used to form experimental crusts. Dust emissions were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…However, we know a priori that there are at least two very weak assumptions in the dust emission modeling: that the soil surface is covered homogeneously with an infinite supply of loose erodible material, which when mobilized by sufficient wind friction, causes dust emission. This approach assumes energy‐limited dust emission which is rarely justified in dust source regions where the soil surface is rough due to soil aggregates, rocks, or gravel, sealed with biological or physical crusts, or loose sediment is simply unavailable (Vos et al., 2020; Webb & Strong, 2011). Consequently, we follow the recently established approach (Hennen et al., 2022) and bypass those weak assumptions by using observed dust emission frequencies at DPS data locations to parameterize the entrainment threshold frequency distribution QDPS(ω)=Cρagus30.25emP(DPS>0), ${Q}_{\text{DPS}}(\omega )=C\frac{{\rho }_{a}}{g}{u}_{s\ast }^{3}\,P(\text{DPS} > 0),$ FDPS(ω)=dAsAfMQDPS100.134clay%6.00.25emwith0.25em0%0.25em<0.25emclay%0.25em<20%, ${F}_{\text{DPS}}(\omega )={\sum }_{d}{A}_{s}{A}_{f}M{Q}_{\text{DPS}}{10}^{\left(0.134{\text{clay}}_{\%}-6.0\right)}\,\text{with}\,0\%\,< \,\text{clay}\%\,< 20\%,$ using the established calibration for this region (Hennen et al., 2022) Log10)(AEMcal=0.880.25emLog10)(FDPS2.02, ${\mathrm{Log}}_{10}\left({\text{AEM}}_{\text{cal}}\right)=0.88\,{\mathrm{Log}}_{10}\left({F}_{\text{DPS}}\right)-2.02,$ where AEM cal is the adjustment of modeled F DPS values using the calibration.…”
Section: Methods and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…However, we know a priori that there are at least two very weak assumptions in the dust emission modeling: that the soil surface is covered homogeneously with an infinite supply of loose erodible material, which when mobilized by sufficient wind friction, causes dust emission. This approach assumes energy‐limited dust emission which is rarely justified in dust source regions where the soil surface is rough due to soil aggregates, rocks, or gravel, sealed with biological or physical crusts, or loose sediment is simply unavailable (Vos et al., 2020; Webb & Strong, 2011). Consequently, we follow the recently established approach (Hennen et al., 2022) and bypass those weak assumptions by using observed dust emission frequencies at DPS data locations to parameterize the entrainment threshold frequency distribution QDPS(ω)=Cρagus30.25emP(DPS>0), ${Q}_{\text{DPS}}(\omega )=C\frac{{\rho }_{a}}{g}{u}_{s\ast }^{3}\,P(\text{DPS} > 0),$ FDPS(ω)=dAsAfMQDPS100.134clay%6.00.25emwith0.25em0%0.25em<0.25emclay%0.25em<20%, ${F}_{\text{DPS}}(\omega )={\sum }_{d}{A}_{s}{A}_{f}M{Q}_{\text{DPS}}{10}^{\left(0.134{\text{clay}}_{\%}-6.0\right)}\,\text{with}\,0\%\,< \,\text{clay}\%\,< 20\%,$ using the established calibration for this region (Hennen et al., 2022) Log10)(AEMcal=0.880.25emLog10)(FDPS2.02, ${\mathrm{Log}}_{10}\left({\text{AEM}}_{\text{cal}}\right)=0.88\,{\mathrm{Log}}_{10}\left({F}_{\text{DPS}}\right)-2.02,$ where AEM cal is the adjustment of modeled F DPS values using the calibration.…”
Section: Methods and Datamentioning
confidence: 99%
“…However, we know a priori that there are at least two very weak assumptions in the dust emission modeling: that the soil surface is covered homogeneously with an infinite supply of loose erodible material, which when mobilized by sufficient wind friction, causes dust emission. This approach assumes energy-limited dust emission which is rarely justified in dust source regions where the soil surface is rough due to soil aggregates, rocks, or gravel, sealed with biological or physical crusts, or loose sediment is simply unavailable (Vos et al, 2020;Webb & Strong, 2011). Consequently, we follow the recently established approach (Hennen et al, 2022) and bypass those weak assumptions by using observed dust emission frequencies at DPS data locations to parameterize the entrainment threshold frequency distribution…”
Section: Dust Emission Model Evaluation Against Dod and Calibration A...mentioning
confidence: 99%
See 1 more Smart Citation
“…As a rule, the intensity of rain at this time is low, but drops of light rain have a greater destructive power than drops of intense rain, because in the latter case, intense rainfall results in a thin layer of water covering the soil, which has a protective function. In low-intensity rainfall, no protective layer of water is formed, the soil aggregates are destroyed and the soil is crusted due to colmatation [66]. The soil crust has a poor capacity for water infiltration, so it activates the lateral runoff [67], which greatly increases the role of microrelief as a factor regulating the distribution of moisture in space [68].…”
Section: Discussionmentioning
confidence: 99%
“…In supplylimited areas, once these fine materials are deposited, there exists a finite period of increased dust emission potential. During the intervening periods, supply is either exhausted or protected from erosive winds by the formation of biogeophysical crusts (Vos et al, 2020) or surface 'armouring'. Accordingly, dust source areas, like the Sistan Basin, Tigris-Euphrates Basin (Syria/Iraq), and the Kuiseb River catchment (Namibia), where ephemeral or fluvial systems (with variable flow rates) occur, will tend to be limited by the production of fine materials (von Holdt and Eckardt, 2018).…”
Section: Inadequate Assumption Of Infinite Supply Of Fine Sedimentsmentioning
confidence: 99%